The role of the John Bordman lime factory in the socio-economic life of the people in Salvacion, Buenavista, Guimaras. - Pillora, Liezel D
This study focuses on the role of the John Bordman Lime Factory on the socio-economic life of the people in Salvacion, Buenavista, Guimaras. It aims to describe the historical development of the John Bordman Factory within the context of the national lime industry. In addition, this study helps to find the contributions of the John Bordman Lime Factory in the socio-economic life of the people in the community. This study also identifies the influence of the lime factory in the development of institutions and infrastructures in the locality during the period., This study was conducted in Salvacion, a barangay in the town of Buenavista in the province of Guimaras where the John Bordman Lime Factory is located. The researcher used an interview schedule in gathering data as well as relevant documents in the municipal office and other pertinent sources. Majority of the employees in the John Bordman Lime Factory is drawn from the natives of the barangay while others came from the adjacent barangays. The establishment of the John Bordman Lime Factory brought about advantages not only to the workers but also to the community as a whole. One of its advantages is through the employment that it generates to the people in the community. The taxes and transport fees that the factory is paying adds to the income of the barangay and at the same time to the town.